Mitos Maklaci Di Desa Angseri, Kecamatan Baturiti: Analisis Struktur, Fungsi Dan Makna - Raditia Indah Sari, Ni Luh Made; Duana Sutika, I Nyoman; Agung Mulyawati, Tjok. Istri (Humanis, 2016)
This study entitled "The Myth Angseri Maklaci Village, Baturiti District; Analysis of Structure, Function and Mean". This study uses a structural theory, the theory of functions and the theory of semiotics. This study aimed to describe the narrative structure contained in the mythical village maklaci Angseri and analyze the function and meaning contained in the maklaci myth. Stage method of providing data used refer assisted with technical notes. Besides, it also assisted with the interview methods and techniques note recording technique, which noted the important things gained from the interview. Furthermore, in the stage of data analysis used qualitative methods. In this phase also supported by the descriptive and analytical techniques. At the stage of presentation of the data analysis, the methods used are informal. Narrative structure which builds myth Angseri maklaci Village, Baturiti District there are five, that is, incidents, flow/plot, character, theme and background. In maklaci myths are a series of ceremonies that includes a special ceremony, maklaci process that consists of the permit application process ( pakeling ), the process of ratification ceremony ( meragat ) and the implementation process of the ceremony, as well as means upakara (offerings). The functions contained in the myth maklaci that is (1) Tri Hita Karana function, (2) the function of the customs, and (3) social functioning society, while meaning that there is the myth maklaci is (1) a religious meaning, the meaning of public welfare, and preservation of cultural significance.